2016
DOI: 10.1084/jem.20150568
|View full text |Cite
|
Sign up to set email alerts
|

IL-1–induced Bhlhe40 identifies pathogenic T helper cells in a model of autoimmune neuroinflammation

Abstract: Lin et al. show that Bhlhe40 expression identifies encephalitogenic CD4+ T helper cells and define a pertussis toxin–IL-1–Bhlhe40 pathway active in experimental autoimmune encephalomyelitis, a mouse model of multiple sclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
112
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(125 citation statements)
references
References 67 publications
13
112
0
Order By: Relevance
“…These authors also found that transmigration through the blood-spinal cord barrier triggered pro-IL-1β expression by neutrophils, and that at day seven after EAE induction, IL-1β-producing neutrophils were found in the blood. We and others also found IL-1β-producing myeloid cells in peripheral lymphoid organs at days five through eight following EAE induction (31, 32, 36, 62). These reports collectively identified a population of CD11b + Ly6C mid-hi MHC II lo-hi monocyte-derived DC/macrophages (moDCs/Macs) as the main source of IL-1β in draining lymph nodes (DLNs), and showed that these cells increase dramatically following MOG 35-55 /CFA immunization given with PTX coadjuvant.…”
Section: Cellular Sources Of Il-1β In Eaesupporting
confidence: 73%
“…These authors also found that transmigration through the blood-spinal cord barrier triggered pro-IL-1β expression by neutrophils, and that at day seven after EAE induction, IL-1β-producing neutrophils were found in the blood. We and others also found IL-1β-producing myeloid cells in peripheral lymphoid organs at days five through eight following EAE induction (31, 32, 36, 62). These reports collectively identified a population of CD11b + Ly6C mid-hi MHC II lo-hi monocyte-derived DC/macrophages (moDCs/Macs) as the main source of IL-1β in draining lymph nodes (DLNs), and showed that these cells increase dramatically following MOG 35-55 /CFA immunization given with PTX coadjuvant.…”
Section: Cellular Sources Of Il-1β In Eaesupporting
confidence: 73%
“…Further, we detected a number of transcription factors that were differentially expressed in Csf1 + compared to Csf1 - T cells (S2 Table); it may be that one or more of these acts in concert with TBET to exert a distinct transcriptional program in Csf1 + cells. Indeed, one of the differentially expressed transcription factors in our dataset, Bhlhe40 , was recently shown to drive GM-CSF expression in a fraction of Th1 and Th17 cells during experimental autoimmune encephalitis [7981]. Previous studies on the gene expression profiles of CD4 + T cells polarized in vitro detected Csf1 transcript in Th2 cells [82], and found no defect in Csf1 expression in Bhlhe40 -deficient CD4 + T cells [80]; however, given that we detected little Csf1 expression in cells polarized in vitro relative to those isolated from infected mice, we hypothesize that these previous gene expression studies lack a robust positive control for Csf1 expression, and instead are measuring relatively low levels of transcript that may not be physiologically meaningful.…”
Section: Discussionmentioning
confidence: 99%
“…The IL-1R1 signaling pathway has received a renewed attention due to its recently reported induction of transcription factor Bhlhe40 associated with Th17 cell encephalitogenic phenotype and GM-CSF secretion (38). Furthermore, the role of IL-1 signaling in the generation of autoimmune responses was most recently documented by the production of IL-1 by neutrophils and monocytes as they migrate to the CNS and induce IL-1R signaling in endothelial cells, which trigger the release of proinflammatory cytokines and chemokines that enhance neutrophil and monocyte recruitment and further T cell recruitment to the CNS (39).…”
Section: Discussionmentioning
confidence: 99%